WEBVTT
00:00:00.920 --> 00:00:13.720
Given that π₯ is equal to five divided by root seven minus root two and π¦ is equal to root seven minus root two, find π₯ plus π¦ expressing your answer in simplest form.
00:00:14.240 --> 00:00:23.320
Before we can add π₯ and π¦, we need to rationalize the fraction π₯ β five divided by root seven minus root two.
00:00:24.000 --> 00:00:35.000
In order to rationalize this, we must multiply the top β the numerator β and the bottom β the denominator β by root seven plus root two.
00:00:35.480 --> 00:00:44.320
This gives us five multiplied by root seven plus root two divided by root seven minus root two multiplied by root seven plus root two.
00:00:44.880 --> 00:00:51.320
Expanding the parenthesis on the numerator gives us five root seven plus five root two.
00:00:52.120 --> 00:00:59.400
In order to expand the parentheses on the bottom, we need to use the FOIL method.
00:01:00.160 --> 00:01:05.440
Multiplying the first terms root seven multiplied by root seven gives us seven.
00:01:06.120 --> 00:01:13.000
Multiplying the outside terms root seven multiplied by root two gives us root 14.
00:01:14.080 --> 00:01:19.080
Multiplying the inside terms gives us negative root 14.
00:01:19.960 --> 00:01:24.160
And finally, multiplying the last terms gives us negative two.
00:01:24.960 --> 00:01:32.920
As the root 14s cancel, weβre left with seven minus two, which is equal to five.
00:01:33.600 --> 00:01:36.040
Therefore, the denominator is equal to five.
00:01:36.880 --> 00:01:40.520
All three of these terms are divisible by five.
00:01:41.680 --> 00:01:56.840
This means that π₯ can be rewritten as root seven plus root two as five root seven divided by five is root seven and five root two divided by five is root two.
00:01:57.480 --> 00:02:02.600
We were told in the question that π¦ was equal to root seven minus root two.
00:02:03.120 --> 00:02:06.480
We now need to add these two expressions.
00:02:07.160 --> 00:02:14.120
Adding the two expressions gives us root seven plus root two plus root seven minus root two.
00:02:15.000 --> 00:02:23.000
Root seven plus root seven is equal to two root seven and root two minus root two is equal to zero.
00:02:23.960 --> 00:02:30.400
This means that the expression for π₯ plus π¦ in its simplest form is two root seven.